Combinatorial Combination Synergism Of Augmentin And Diclofenac Dosage Forms Against Community And Methicillin Resistant Staphylococcus Aureus (Journal of Pharmaceutical Negative Results, 2023)
One of the approaches of combinatorial chemistry is to get new derivatives help in human health well-being. Treatment of the infectious disease via fighting the responsible pathogenic bacteria is one of combinatorial chemistry targets. The rate of resistance of Staphylococcus aureus bacterial strains to the most common antibiotics is increasing massively. This study aimed to assess the synergistic effect of a combination between the most common used non-steroidal anti-inflammatory agents and antibiotic in Al-Bayda city against pathogenic Gram-negative bacteria. In this study, Diclofenac Sodium 50mg and Diclofenac Potassium 50mg separately and in combination with Amoxicillin & Clavulanic Acid 625mg were tested for if they have any synergistic effect against both community Staphylococcus aureus; Methicillin sensitive Staphylococcus aureus and Methicillin resistant Staphylococcus aureus (MRSA). The Well Diffusion Method was used to assess the antibacterial activity. The results showed that the the different combination between Amoxicillin & Clavulanic Acid 625mg + Diclofenac Potassium 50mg + Diclofenac Sodium 50mg exhibited more inhibitory potency against both tested bacteria. Diclofenac Sodium 50mg showed higher synergistic effect against Methicillin resistant Staphylococcus aureus (MRSA). In conclusion, this study proved that combinations of Augmentin with the tested non-steroidal drugs showed clear inhibitory activity on the tested community Staphylococcus aureus and Methicillin resistant Staphylococcus aureus compared to the inhibition activity showed from the tested antibiotics alone.